Bilateral diffuse grade 5 radiation pneumonitis after intensity modulated radiation therapy for localized lung cancer - Osborn, Virginia W (World J Clin Oncol, 2017)
We are reporting a case of fatal radiation pneumonitis that developed six months following chemoradiation for limited stage small cell lung cancer. The patient was a 67-year-old man with a past medical history of Hashimoto’s thyroiditis and remote suspicion for CREST, neither of which were active in the years leading up to treatment. He received 6600 cGy delivered in 200 cGy daily fractions via intensity modulated radiation therapy with concurrent cisplatin/etoposide followed by additional chemotherapy with dose-reduced cisplatin/etoposide and carboplatin/etoposide and then received prophylactic cranial irradiation. The subsequent months were notable for progressively worsening episodes of respiratory compromise despite administration of prolonged steroids and he ultimately expired. Imaging demonstrated bilateral interstitial and airspace opacities. Autopsy findings were consistent with pneumonitis secondary to chemoradiation as well as lymphangitic spread of small cell carcinoma. The process was diffuse bilaterally although his radiation was delivered focally to the right lung and mediastinum.